#HashtagSolidarities: Twitter debates and networks in the MENA region - Mareike Transfeld; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2016)
During the course of the so-called Arab Spring, observers were quick to refer to the uprisings as "Facebook revolutions" or "Twitter revolutions". Although the important role of social media in the 2011 upheavals in the Middle East and North Africa (MENA) is widely acknowledged, its impact on political processes in the region remains contested and contradictory. Rather than looking at social media through a transformation or security lens, the research presented here focused on how debates on three events in the MENA region - the emergence of a video of a rape on Cairo's Tahrir Square in June 2014, anti-fracking protests in southern Algeria in early 2015, and Saudi Arabia's military intervention in Yemen in March 2015 - unfolded on Twitter. Closely tracing Twitter debates on these incidents shed light on Twitter's role in important social and political discussions as well as on the scope and patterns of Twitter networks and digital solidarities. In other words, it highlighted the various ways in which Twitter was used by ordinary people, activists, media outlets, and officials, and in doing so, it provides an idea of the political impact such debates can have via Twitter. The research also revealed that the breadth of opinion on Twitter far exceeds that of traditional media in the MENA region, and the more repressive a context, the more important Twitter becomes. Furthermore, Twitter, in forging digital solidarities, contributes to deepening existing social and political cleavages. That is, the platform is not an autonomous digital space following logics different from those in the physical world. Rather, the dynamics of Twitter are strongly driven by local historical experience, social patterns, and national politics. (SWP Research Paper)
Keywords: 320; Naher und Mittlerer Osten und Nordafrika; Near and Middle East and North Africa; Europäische Union; European Union